Net-tension strength of double-lap joints under bearing-bypass loading conditions using the cohesive zone model. (January 2015) - Kabeel, A.M.; Maimí, P.; González, E.V.; Gascons, N.
Abstract: Tensile failure is a primary failure mode in structures with multi-fastener joints specially for large bypass loads. Therefore, the precise prediction of the net-tension strength of these joints is essential for reliable design of many engineering structures. In this paper the analytical model presented by Kabeel et al. (2014) has been extended to predict the net-tension strength of double-lap joints under combined bearing-bypass loading conditions. Due to the ability of the cohesive law to predict the effect of the structure size on its strength, the present model is formulated based on the cohesive zone model. The effect of the bypass stresses on the joint net-tension strength has been studied. The present model is able to predict the optimum geometry of the joints and, consequently, its maximum nominal strength. A comparison of the obtained predictions with those of the available experimental work reveals good agreement. The obtained results can be used as design charts for the double-lap joints that are made of isotropic quasi-brittle materials.